PENGARUH JUMLAH ASAM SITRAT, SUHU DAN WAKTU PENGEMPAAN TERHADAP SIFAT PAPAN PARTIKEL DARI PELEPAH KELAPA SAWIT - , KARUNIA AGUS; , D.Agr.Sc. Ragil Widyorini, ST, MT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Oil palm frond, as one of potential biomass waste, can be used as raw materials of particleboard. Manufacture of binderless particleboard is an alternative eco-friendly technologies that can be done to optimize the potential of oil palm frond. Citric acid was develop as natural adhesive materials to increase particleboard properties. Quality of particleboard is affected by several factors such as temperature pressing and time. This study was intended to investigate the effect of citric acid, pressing temperature, and time on physical and mechanical properties of particleboard. This study was using completely randomized design into three different factors, amount of citric acid (0% and 10%), pressing temperature (200ËC and 220ËC) and pressing time (10 min and 15 min). The research material is oil palm frond from Ujung Tanjung, Rokan Hlir, Riau. Particleboard properties of was evaluated acconding to JIS A 5908-2003 (type-8) including : density test, moisture content, water absorption, thickness swelling, internal bonding, modulus of rupture, and modulus of elasticity. The results showed that the addition of 10% citric acid provided a very significant effect on water content, water absorption, thickness sweeling and internal bonding, as well as the modulus of elasticity give real effect to the particleboard. Based on this study the addition of citric acid can enhance physical and mechanical properties of particleboards manufactured from palm oil frond. Whereas the best treatment was obtained by 10% citric acid at pressing temperature of 200ËC for 10 minutes with the following value